Impact of Anticyclonic Eddy on Nonlinear Wave‐Wave Interaction in the Southern South China Sea During Late Summer 2020. Issue 9 (5th May 2022) - Xu, Hongzhou; Zhang, Zhipeng; Vetter, Philip Adam; Xie, Qiang; Long, Tong; Hong, Bo
Abstract: Nonlinear wave‐wave interaction (WWI) in the southern South China Sea (SCS) has rarely been investigated due to sparse field observation. By analyzing datasets recorded by two adjacent moorings, we find active nonlinear WWI among diurnal internal tides (D1 ITs), near‐inertial waves (NIWs), and D1‐f waves in this area. Although the blue shift of NIWs can provide part of the energy for D1‐f waves, the bulk of D1‐f energy was generated from the nonlinear WWI. Driven by the summer monsoon, a dipole of mesoscale eddies was formed off the central Vietnam coast and intruded into the study area. The anticyclonic eddy of the dipole reduced the local effective Coriolis frequency by providing negative vorticity and suppressed the nonlinear WWI locally. During the intrusion period, D1‐f waves almost vanished suggesting the important role of mesoscale eddy on adjusting the nonlinear WWI in the SCS. Plain Language Summary: Nonlinear wave‐wave interaction (WWI) n is a common phenomenon in the global ocean and it can transfer energy among wave motions with different spatial and temporal scales. Therefore, it plays important role in energy cascade and modulating global ocean circulation. In the high latitude of the northern South China Sea (SCS), nonlinear WWI has been studied extensively since the strongest internal wave over the world was triggered there. However, it was rarely concerned in the low latitude of the SCS. Based on direct field observation and data analysis, active WWI was found in the southern SCS. And the energy transfer mainly occurred among waves with the frequencies from near‐inertial to diurnal motions. Cyclonic/anticyclonic eddy can enhance/weaken nonlinear WWI largely through input of positive/negative vorticity. The anticyclonic eddy of the dipole off the central Vietnam coast almost determined the nonlinear WWI in the southern SCS during summer monsoon season. These spotlight the impact of background circulation on the WWI in the SCS. Key Points: Active nonlinear wave‐wave interaction among triad waves was observed in the southern South China Sea Nonlinear wave‐wave interaction provided bulk energy for generating D1‐f waves Anticyclonic eddy suppressed nonlinear wave‐wave interaction and reduced near‐inertial waves and D1‐f waves largely